Dietary supplementation with Lactium and L-theanine alleviates sleep disturbance in adults: a double-blind, randomized, placebo-controlled clinical study - Lim, Su Eun; Kim, Ho Seok; Lee, Siwoo; Kang, Eun Young; Lim, Jong-Hyun; Kim, Byung-Yong; Shin, Seon-Mi; Baek, Younghwa (Frontiers in Nutrition, 2024)
The use of natural products for the treatment of sleep disturbances is increasing owing to the side effects and limitations of traditional sleep therapy. Moreover, recent studies have shown a significant correlation between sleep quality and gut microbiota composition. This study aimed to assess the impact of LTC-022, a commercially available dietary supplement containing Lactium and L-theanine, on enhancing sleep quality.Methods: Forty participants experiencing sleep discomfort were enrolled in a double-blind randomized controlled trial, wherein they received LTC-022 or a placebo orally for 8 weeks. The effects of treatment on sleep quality were assessed using the Pittsburgh Sleep Quality Index and Insomnia Severity Index. To comprehensively evaluate changes in sleep patterns, various parameters were evaluated, including the time in bed (TIB), total sleep time (TST), sleep onset latency (SOL), sleep efficiency (SE), wake after sleep onset (WASO) counts, and bedtime. These parameters were derived from daily sleep logs recorded over the 8-week study period, categorized into weekdays and weekends. Stool samples were analyzed for microbiome composition. The V4 region of bacterial 16S rRNA genes was amplified using specific primers (515F and 806R) and targeted for analysis. Microbial diversity, including operational taxonomic units, the Shannon and Chao indices, the Firmicutes/Bacteroidetes (F/B) ratio, and the variety of bacterial taxa, was assessed.Results: No significant differences were observed in sleep quality and insomnia scale characteristics between the two groups. In-depth analysis using sleep diaries showed that WASO counts after 8 weeks and bedtime after 4 weeks showed significant differences between the LTC-022 and control groups. In the LTC-022 group, significant differences were observed in the increase in TST, decrease in SOL, increase in SE, decrease in WASO counts, and earlier bedtime. Microbiome analysis revealed that the abundance of the genera Blautia and Ruminococcus increased in fecal samples from the LTC-022 group.Conclusions: These results suggest that continuous LTC-022 intake has a beneficial effect on maintaining sleep duration and an appropriate bedtime. Additionally, changes in the gut microbiota may be linked to changes in sleep patterns resulting from the consumption of Lactium and L-theanine.